Visionary Leadership and Dynamic Capabilities: Transforming Pesantren into a Social Enterprise - Thoha, A. Faiz Khudlari (UNISSULA, 2024)
In the dynamic landscape of Indonesia's education and community development, Pesantren (Islamic boarding schools) have been traditional beacons of spiritual and moral guidance. Amidst evolving socio-economic challenges, these institutions are increasingly adopting the mantle of social entrepreneurship to extend their influence and impact. This study explores the transformation of Pesantren Riyadlul Jannah Pacet into a social enterprise, emphasizing the critical role of visionary leadership and dynamic capabilities. Utilizing a qualitative case study approach, it investigates how the Pesantren adapts and innovates while retaining its core religious and educational values. The research, through extensive interviews, observations, and document analysis, unveils the strategies and initiatives that have led to significant community and socio-economic advancements. It offers profound insights into the integration of traditional religious education with contemporary entrepreneurial practices, highlighting the potential of Pesantrens as agents of sustainable change and innovation. This study contributes to the broader discourse on the adaptive and transformative capacity of educational institutions in the face of societal needs and opportunities.